STEREOTIFIKASI PEREMPUAN DALAM IKLAN PERBANKAN (PEMBACAAN SEMIOTIKA JUDITH WILLIAMSON PADA IKLAN MANDIRI ONLINE) - Andreas, Rino (JURNAL ILMU BUDAYA, 2021)
Advertising is not a neutral media, but rather a part of the dominant discourse. This paper focuses on elaborating ideologies in three Mandiri Online advertisements using Judith Williamson's semiotic analysis. The result, shows that Mandiri Online ads reproduce public awareness by representing women as a social group that likes to shop and fetishist of the commodities they want. The stereotype is attached as natural. Mandiri Online ads also perpetuate a culture of consumerism with products that offer transactions via online. Furthermore, the advertisements chose artists like Tara Basro and Reza Rahardian who are already well-known as young artists and performers in the Indonesian film industry. Bank Mandiri "borrows" the meaning of popularity, youth and achievement, so that the product obtains a significant meaning based on the artist's reference system.